The end of welfare states as we know them? A multidimensional perspective - Jakub Sowula; Franziska Gehrig; Lyle A. Scruggs; Martin Seeleib-Kaiser; Gabriela Ramalho Tafoya (Luxembourg Income Study (LIS), 2023)
This article highlights the limitations of unidimensional analyses in the comparative welfare state literature and emphasises the need for a more holistic, multidimensional approach incorporating social spending, welfare state outputs, and outcomes. To illustrate the utility of a multidimensional approach, we examine the long-term welfare state trajectories of Sweden and Germany, prototypical socialdemocratic and conservative welfare states, respectively, and compare them against the baseline of Europe's prototypical liberal welfare state, the United Kingdom. The social spending (expenditure) and output (generosity) allowed us to identify significant changes in the Swedish welfare state (i.e., retrenchment). The outcome dimension alerts us to a policy drift in the German Welfare State, as relatively stable public spending and welfare generosity until the first half of the 2000s were nonetheless associated with sharply increased inequality and poverty. Overall, our findings suggest that a holistic, multidimensional approach is necessary to fully understand the complexities of welfare state change and continuity, as focusing solely on one dimension can lead to analytical misjudgments. The sharp rise in inequality and poverty across countries raises doubts about whether policymakers and researchers rely too much on outdated assumptions of normality that fail to meet the welfare state realities of today.
Keywords: 330; Multidimensional Welfare State Change; Social Spending; Generosity; Poverty and Inequality; UK; Germany; Sweden; Welfare Regimes